Customer centricity and guanxi prevalence as social capital: a study of international business relationships. Issue 8 (1st October 2018) - Scheinbaum, Angeline Close; Wang, Stephen W.
Abstract : Purpose: This research blends perspectives of the Eastern phenomenon of guanxi with the more Western perspectives of relationship marketing and customer centricity. Extending scholarship on guanxi in marketing (e.g.Park and Luo, 2001 ;Sheu and Hu, 2009 ;Luo et al ., 2008 ;Fowler and Reisenwitz, 2014 ), the objective is to highlight the indirect role of customer centricity (i.e. how visible or central it is for the business partner to communicate with/have information sharing with), for firms in regions with a prevalence of guanxi. Design/methodology/approach: The empirical model is tested in context of global marketing in the business-to-business (B2B) logistics industry ( n = 508). A total of 508 global logistics employees and managers with experience in global business participated in the survey in Taiwan. Structural equation modeling was used for data analysis with multi-group analyses. Findings: Customer centricity intensifies positive outcomes of guanxi prevalence. Specifically, a high level of customer centricity strengthens established associations among guanxi prevalence, trust, relationship commitment and firm performance. Originality/value: While most work on guanxi has a focus in China, this research focuses on Taiwan. While building on a wealth of literature, relatively less work has focused on customer centricity.